2017
DOI: 10.3390/separations4010008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Miniaturized and Conventional Asymmetrical Flow Field-Flow Fractionation (AF4) Channels for Nanoparticle Separations

Abstract: Abstract:The performance of a miniaturized channel for the separation of polymer and metal nanoparticles (NP) using Asymmetrical Flow Field-Flow Fractionation (AF4) was investigated and compared with a conventional AF4 system. To develop standard separation methods, experimental parameters like cross flow, gradient profile and injection time were varied and optimized. Corresponding chromatographic parameters were calculated and compared. Our results indicate that the chromatographic resolution in the miniaturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Besides the mathematical approaches, changes in AF4 hardware for improvement in analysis time and speed were recently investigated. Although a miniaturized channel can shorten analysis time and lower solvent consumption, the chromatographic resolution in the miniaturized channel is lower . On the other hand, a proof-of-concept study demonstrated that retention time, selectivity and resolution can be increased in AF4 by introduction of microstructured ultrafiltration membranes at the collection wall .…”
Section: Size-based Separations Of Synthetic Polymersmentioning
confidence: 99%
“…Besides the mathematical approaches, changes in AF4 hardware for improvement in analysis time and speed were recently investigated. Although a miniaturized channel can shorten analysis time and lower solvent consumption, the chromatographic resolution in the miniaturized channel is lower . On the other hand, a proof-of-concept study demonstrated that retention time, selectivity and resolution can be increased in AF4 by introduction of microstructured ultrafiltration membranes at the collection wall .…”
Section: Size-based Separations Of Synthetic Polymersmentioning
confidence: 99%